2011
DOI: 10.3892/ijo.2011.1196
|View full text |Cite
|
Sign up to set email alerts
|

Tumor suppressive microRNA-375 regulates lactate dehydrogenase B in maxillary sinus squamous cell carcinoma

Abstract: Abstract. The expression of is significantly reduced in cancer tissues of maxillary sinus squamous cell carcinoma (MSSCC). The aim of this study was to investigate the functional significance of miR-375 and a possible regulatory role in the MSSCC networks. Restoration of miR-375 significantly inhibited cancer cell proliferation and invasion in IMC-3 cells, suggesting that miR-375 functions as a tumor suppressor in MSSCC. Genome-wide gene expression data and luciferase reporter assays indicated that lactate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 34 publications
(51 reference statements)
0
26
0
Order By: Relevance
“…Heightened expression of LDHB may contribute to tumor acidity, and growth (24) known to occur in parallel to activated RTK-PI3K-AKT-mTOR signaling (25) and is observed in various types of cancer including bladder (26) merkel cell carcinoma (27) lung cancer (28) glioma (29) or maxillary sinus squamous cell carcinoma, most reporting its association with poor survival rates (30). …”
Section: Discussionmentioning
confidence: 99%
“…Heightened expression of LDHB may contribute to tumor acidity, and growth (24) known to occur in parallel to activated RTK-PI3K-AKT-mTOR signaling (25) and is observed in various types of cancer including bladder (26) merkel cell carcinoma (27) lung cancer (28) glioma (29) or maxillary sinus squamous cell carcinoma, most reporting its association with poor survival rates (30). …”
Section: Discussionmentioning
confidence: 99%
“…Ectopic overexpression of miR-375 impairs cell invasion of oral cavity, hypopharyngeal, nasopharyngeal, esophageal, breast, hepatocellular, cervical, and gastric cancer cells. 15,20,22,23,6569 Our previous study 11 reported that stable increased miR-375 expression in both UMSCC1 and UMSCC47 cell lines results in diminished invasion in vitro. The invasive nature of HNSCC is often associated with locoregional invasion and metastasis to cervical lymph nodes.…”
Section: Commentmentioning
confidence: 99%
“…In the present study, we found a higher expression of miR-375 and miR-487b in the HA group, which indicated that high concentration of astaxanthin could suppress tumor growth by inducing overexpression of miR-375. Also, several studies have shown that the expression of miR-375 is significantly reduced in tumor tissues, and this miRNA functions as a tumor suppressor by targeting several oncogenic genes [48,49,50,51,52]. On the other hand, miR-487b has an important role as a tumor-suppressive by inhibiting cell proliferation, invasion, and migration, and has been mapped to 14q32.31 in metastatic PCa cells [53].…”
Section: Discussionmentioning
confidence: 99%